Persepsi Manajer Perawat tentang Keselamatan Pasien - Wiranata, I Nyoman; Swarjana, I Ketut; Negara, I Gusti Ngurah Made Kusuma; Nuartini, Ni Nyoman (Journal of Telenursing (JOTING), 2023)
This study aims to review the scope of the role of nurse managers in managing patient safety in hospitals. The method used was a literature review. There were 12 articles analyzed obtained from online databases on Pubmed, Science Direct, and other sources. The results of this study indicate that nurse managers have a high perception and positive attitude toward patient safety culture, and the leadership climate in the hospital creates a patient safety culture. In conclusion, nurse managers have a high perception of patient safety, and nurse managers' leadership styles and strategies play a role in increasing nursing staff's perception of patient safety and patient safety culture. Keywords: Patient Safety, Nurse Manager, Hospital